Determinan Ketepatan Waktu dalam Penyampaian Laporan Pertanggungjawaban Keuangan pada Komisi Pemberantasan Korupsi - Safitri, Karyani; Sasongko, Mochamad Agung (PUTRA JAWA PUBLISHER, 2025)
In its implementation, the State Budget (APBN) must be carried out in an orderly manner, adhering to laws and regulations, while being productive, economical, effective, transparent, and responsible. Therefore, it is necessary to prepare timely reports on the utilization of the APBN, aligning with the principle of timeliness in reporting. The objective of this research is to analyze how the use of information technology, the competence of employees, and internal controls impact the promptness of financial reporting. A quantitative method is employed in this study. The object of this research is the Persons in Charge (PIC) responsible for preparing and compiling financial accountability reports at the Corruption Eradication Commission (KPK). The primary data were collected through questionnaires. The study involved 90 respondents out of a total population of 117, selected using purposive sampling. Data analysis was conducted using validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, t-tests, f-tests, and R-square tests, utilizing IBM SPSS (Statistical Package for the Social Sciences) version 27. The results show that the utilization of information technology, human resource competence, and internal control positively and significantly influence the timeliness of financial accountability reporting. This study is limited to the work unit of the Corruption Eradication Commission (KPK), suggesting that results may vary if conducted in other government work units.